Social characteristics of a child formed in the family during early childhood (Zien Journal of Social Sciences and Humanities, 2024)
This article discusses the formation of a child's social characteristics in early childhood and the impact of the child's social development in the family on the formation of relationships between representatives of the older generation and family members